MEDIA DAN PREFERENSI PILIHAN POLITIK GENERASI Z PADA PILPRES 2024 MENUJU DEMOKRASI DIGITAL YANG BERMARTABAT - Lusi Andriyani; Usni; Fahmi Anggraeni; Ambarwati; Haniah Hanafie (INDEPENDEN: Jurnal Politik Indonesia dan Global, 2025)
Technological developments have brought significant changes to human life, impacting individual situations and social interactions, one example being the general election process. Social media is currently a part of online media, or new media. Its existence has begun to be used as a tool for socialization and political strategy because it is considered more efficient in use, low cost, and offers unlimited access. The use of social media as a medium for political dialogue has been carried out on various occasions. Social media has developed into a new tool with significant implications for everyday life, particularly in the political sphere. All issues are easily accessible through information on social media. In this context, social media has ultimately become a tool for Gen Z to obtain information and political literacy, which influences their political preferences and political choices. The digitalization of information is an unavoidable process and will pose a challenge to the implementation of democracy in Indonesia. Keywords: Social media, Gen-Z, Political preferences, 2024 presidential election, Digital democracy.